Continuity of medication information transfer and continuous medication supply during hospital-to-home transitions - nationwide surveys in hospital and community pharmacies after implementing new legal requirements in Germany - Klasing, Sophia; Dörje, Frank; Hilgarth, Heike; Metzger, Nadine; Richling, Ina; Seidling, Hanna (BMC health services research, 2024)
While successful information transfer and seamless medication supply are fundamental to medication safety during hospital-to-home transitions, disruptions are frequently reported. In Germany, new legal requirements came into force in 2017, strengthening medication lists and discharge summaries as preferred means of information transfer. In addition to previous regulations - such as dispensing medication at discharge by hospital pharmacies - hospital physicians were now allowed to issue discharge prescriptions to be supplied by community pharmacies. The aim of this survey study was to gain first nationwide insights into how these requirements are implemented and how they impact the continuity of medication information transfer and continuous medication supply.
Gesehen am 15.10.2024